2015
DOI: 10.1007/978-3-319-24264-4_7
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Liquefied Natural Gas Routing and Deteriorating Inventory Management Problem

Abstract: Abstract. Liquefied Natural Gas (LNG) is becoming a more crucial source of energy due to its increased price competitiveness and environmental friendliness. We consider an inventory routing problem for inland distribution of LNG from storage facilities to filling stations. Here, an actor is responsible for the inventory management at the storage facilities and filling stations, as well as the routing and scheduling of a heterogeneous fleet of vehicles. A characteristic of the problem is that a constant rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The LNG-DIRP is NP-hard since it is an extension of the classical IRP. Ghiami et al (2015) have shown that only a simplified version of this problem can be solved to optimality for small-size instances. For this reason, we have developed a matheuristic to solve the problem and aim at obtaining good-quality solutions within reasonable solution times.…”
Section: The Objective Function and Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LNG-DIRP is NP-hard since it is an extension of the classical IRP. Ghiami et al (2015) have shown that only a simplified version of this problem can be solved to optimality for small-size instances. For this reason, we have developed a matheuristic to solve the problem and aim at obtaining good-quality solutions within reasonable solution times.…”
Section: The Objective Function and Constraintsmentioning
confidence: 99%
“…For an overview of deteriorating inventory we refer to Bakker et al (2012) and Janssen et al (2016). Except for LNG-related applications, there is limited literature on deteriorating item inventory-routing problems (IRPs), see Ghiami et al (2015).…”
Section: Introductionmentioning
confidence: 99%
“…Ghiami et al [14] studied the design of the LNG distribution network in the Netherlands. The authors implemented an application on the inventory routing problem.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the models include one type of transportation mode with a single phase of the LNG supply chain. For example, the studies [1,2,5,[7][8][9][10][11][12][13][14][15][16] and [21] include only one type of transportation modes. Studies [3,4,6,[17][18][19] and [20] include two types of transportation modes.…”
Section: Introductionmentioning
confidence: 99%
“…,Ghiami et al (2015),Goel et al (2015),Al-Haidous et al (2016) andMsakni & Haouari (2018) have considered this important constraint in their models. There are also several considered constraints in the optimization models of LNG process design and operations including Berth availability (Halvorsen-Weare & Fagerholt, 2013; Al-Haidous et al, 2016; Andersson et al, 2017; Msakni & Haouari, 2018), ship travel time (Halvorsen et al, 2013; Agra et al, 2015; Zhang et al, 2017; Msakni & Haouari, 2018), maintenance (Al-Haidous et al, 2016; Msakni & Haouari, 2018), bunkering requirements (Al-Haidous et al, 2016;…”
mentioning
confidence: 99%